Chlorophyll fluorescence responses to temperature and water availability in two co-dominant Mediterranean shrub and tree species in a long-term field experiment simulating climate change - Ogaya, Romà; Penuelas, Josep; Asensio, Dolores; Llusia, Joan (Environmental and Experimental Botany, 2011)
A rain exclusion experiment simulating drought conditions expected in Mediterranean areas for the following decades (15% decrease in soil moisture) is being conducted since 1999 in a Mediterranean holm oak forest to study its response to the forecasted climatic changes for the coming decades. The maximum PSII quantum yield of primary photochemistry (Fv/Fm) was measured in Quercus ilex, and Phillyrea latifolia, the co-dominant species of the studied forest, from 1999 to 2009 in four plots: two of them were control plots and the other two plots received the rain exclusion treatment. In both species, the Fv/Fm values were highly dependent on air temperatures, and in a second term, in water availability. P. latifolia was the species with the larger decrease in Fv/Fm values induced by low air temperatures, while in hot seasons, the Fv/Fm values in P. latifolia were even higher than in Q. ilex. Rainfall exclusion decrease Fv/Fm values signiﬁcantly only in few monitoring dates. The most drought resistant species P. latifolia was more affected by the experimental rainfall exclusion than Q. ilex that instead lost number of leaves per tree. There was a synergic effect of drought stress and winter cold in P. latifolia not observed in Q. ilex, but a more conservative strategy in P. latifolia maintaining leaves with a down-regulation of the linear photosynthetic electron transport. These results indicate that, although other physiological and reproductive strategies at whole plant level must be also taken into account, the warmer and drier environment expected for the following decades could favour the species more sensitive to cold and more resistant to drought, the shrub P. latifolia, in detriment of the tree Q. ilex as already observed in the ﬁeld after severe heat-drought episodes.
Keywords: Chlorophyll ﬂuorescence; climate change; Cold; Drought; evergreen leaves; Fv/Fm; Heat; mediterranean forest; phillyrea latifolia; Quercus ilex